In vivo efficacy of lasalocid and pyrimethamine treatments against Anophryoides haemophila, a ciliate pathogen of American lobster Homarus americanus - ATHANASSOPOULOU (Φ. ΑΘΑΝΑΣΟΠΟΥΛΟΥ), F.; CRIBB, A. E.; CAWTHORN, R. J.; MacMILLAN, R.; BALDAS (Γ. ΜΠΑΛΝΤΑΣ), G. (Journal of the Hellenic Veterinary Medical Society, 2017)
Lasalocid and pyrimethamine was administered to American lobsters infected with A. haemophila. Lasalocid was found to be toxic and acute mortality was observed, when administered in vivo in both infected and uninfected lobsters. Pyrimethamine was found very efficient to treat these ciliates at repeated doses. The mortality was very low and the mean haemocyte counts remained higher than the uninfected control group. The drug seems to delay the appearance of the ciliates in the haemolymph and to lower the spread of these parasites in the epipodite and the hepatopancreas. In uninfected animals treated with this drug, haemocyte counts were similar to uninfected control group. Furthermore, no pathology was observed, when the drug was administered to uninfected lobsters. Since there is no effective treatment for the control of bumper car disease, on the basis of the results of the present study, we suggest that pyrimethamine is a good drug for the treatment of A. haemoplila infection in lobsters.